Directions of Organization of Internal Audit Service in Insurance Organizations - Abduraimova Maftunakhon Akhmatovna (Research Parks Publishers, 2021)
This article discusses the main directions of the organization of the internal audit service in insurance companies and the resulting efficiency, the achievements. Suggestions and recommendations were made on the provision of a modern system of corporate governance in the organization of internal audit services in insurance companies, the strengths in the organization of internal audit services in accordance with international standards and the improvement of business processes.